AB0178 IL-12 Inhibits the Production of IL-10 in Patients with Sjogren Syndrome. (9th June 2015) - Yao, G.; Chen, W.; Tang, X.; Feng, X.; Sun, L.
Abstract : Background: Interleukin (IL)-12, IL-23, IL-27, and IL-35 constitute a unique family of structurally-related, heterodimeric cytokines, which regulate immune response and inflammatory reactions. IL-12 family has been reported to be involved in the pathogenesis of autoimmune diseases [1-2] . However, the role of IL-12 family on Sjogren syndrome (SS) and related mechanisms remained to be elucidated. Objectives: Since the IL-12 family has been shown to regulate the generation of T regulatory 1 (Tr1) cells and Tr1 cells have been indicated a functional role in disease progress of SS through their secretion of the immunosuppressive cytokine IL-10 [3-4] . The aim of the present study was to identify the specific members of IL-12 family involved in the pathogenesis of SS and to explore the relationship of IL-12 family cytokines with IL-10. Methods: 20 SS patients, 20 RA patients, 20 SLE patients and 20 healthy volunteers were recruited in the present study. Expressions of IL-12, IL-23, IL-27, and IL-35 in peripheral blood mononuclear cells (PBMCs) from patients with SS, RA, SLE and healthy controls were determined by quantitative PCR. Plasma levels of IL-12, IL-27 and IL-10 were detected by Enzyme-linked Immunosorbent Assay. Results: IL-12 and IL-27 mRNA significantly increased in PBMCs from patients with SS than healthy controls. Increased plasma levels of IL-12 and IL-27 have been confirmed in SS patients. Plasma IL-12 and IL-27 correlated with clinic indexes, such as anti-SSA, anti-SSB and ANA antibodies. IL-12 levels showed a negative correlation with plasma IL-10. However, no significant correlation was found between plasma IL-27 and IL-10 (Fig1 ). Conclusions: These findings suggested that IL-12 might have a pivotal role in the development and progression of SS through suppression of differentiation of IL-10-producing Tr1 cells. Therapeutic targeting IL-12 and Tr1 cells might be useful in the modulating of SS. References: Gee K, Guzzo C, Che Mat NF, et al. The IL-12 family of cytokined in infection, inflammation and autoimmune disorders. Inflamm Allergy Drug Targets, 2009, 8(1):40-52. Vignali DA, Kuchroo VK. IL-12 family cytokines: immunological playmakers. Nat Immunol, 2012, 13(8): 722-8 Tsoumakidou M, Tousa S, Semitekolou M, et al. Tolerogenic signaling by pulmonary CD1c + dendritic cells induces regulatory T cells in patients with chronic obstructive pulmonary disease by IL-27/IL-10/inducible costimulator ligand. J Allergy Clin Immunol, 2014, 134(4): 944-54. Pot C, Apetoh L, Kuchroo VK. Type 1 regulatory cells (Tr1) in autoimmunity. Semin Immunol, 2011, 23(3):202-8. Disclosure of Interest: None declared